MODEL EFEKTIVITAS KERJA DALAM MENUNJANG KINERJA TENAGA PENDIDIK DAN TENAGA KEPENDIDIKAN - Destina Paningrum, Rusnandari Retno Cahyani (Prosiding Seminar Nasional, 2014)
Human resources is a factor in every major problems existing activities in various fields and line ofwork, especially organizational life. Therefore, improving the quality of human resources shouldprovide value to the organization to see how effective it works. This study aims to Develop model development effectiveness in supporting the performance of educators and education personnel. Target outcomes in this study is the first development to work effectively as a reference model of the Personnel Division to improve the performance of educators and education personnel, both Enrichment teaching materials for Human Resources Management courses and three papers presented in national meetings. This study used qualitative methods to social situation that place, actors and activity. This study by sampling the purposive sampling technique.Â